Attenuation, molecular characterization and inactivation of fowl adenovirus isolates propagated in chicken embryo liver cells for vaccine development - Ugwu, Chidozie Clifford (2021)
Fowl adenovirus (FAdV) 8b causes inclusion bodies hepatitis (IBH) in chicken with 10- 30%. mortality worldwide and was first reported in Malaysia in 2005, but control has been difficult due to unavailability of vaccines. The objectives of this study were to propagate Malaysian isolates of FAdV 8b in chicken embryo liver (CEL) cells, attenuate, molecularly characterize and inactivate the virus and determine the pathogenicity, immunogenicity and efficacy of the attenuated and inactivated isolates in commercial broiler chickens. UPM11142, UPM11134 and UPM08136 FAdV isolates from IBH outbreaks in Malaysia were each inoculated into specific pathogen free (SPF) chicken embryonated eggs (CEE). Liver from dead embryo were processed to obtain FAdV inocula which were each propagated and attenuated onto CEL cells till passage 20 (P1-P20). The P5 and P20 of UPM11142 and UPM08136 FAdV were propagated in Cytodex™ 1 microcarrier adapted CEL cells in a stirred tank bioreactor (P5B1 and P20B1). TCID50 of all isolates were determined. Virus infectivity and localization of the virus in CEL cells were determined by immunocytochemical and HE stainning assays. PCR amplification of hexon and fibre genes were carried out using established and novel primers. Amplified genes were sequenced, analysed and phylogenetic trees constructed. UPM11142P5B1 and UPM08136P5B1 isolates were inactivated using binary ethylene imine (BEI) method, adjuvanted with Montanide 71VG and tested for immunogenicity and efficacy (with or without booster) on commercial broiler chickens. UPM11142P20B1 and UPM08136P20B1 attenuated vaccine candidates either with or without booster were tested for pathogenicity, immunogenicity and efficacy in commercial broiler chickens. Challenge group chickens of all groups were challenged with pathogenic FAdV at 28- day post inoculation (dpi). Clinical signs, gross and histopathological changes of organs were recorded. Body weight, liver weight and liver to body weight ratio were recorded. Humoral and cellular immunity were determined by ELISA and flowcytometry, respectively. FAdV challenge virus copy number in cloaca and liver were determined by qPCR. Data generated were analysed using two-way repeated measures ANOVA and means separated with turkey HSD tests on 5% probability level. UPM11142 and UPM11134 isolates caused 100% mortality of SPF CEE, while UPM08136 caused 86%. All isolates caused CPE on CEL cells characteristic of FAdV. FAdV titre ranged from 105.5 – 107.5 TCID50/mL while virus infectivity and localization of virus in the nucleus were observed. These isolates were confirmed as FAdV genotype E, serotype 8b which were 98 to 100% phylogenetically related to UPM04217 reference isolate from GenBank. Sequence analysis of hexon gene revealed nucleotide changes G►31T causing amino acid change V►11L in UPM11142; synonymous C►735T in UPM11134; and G►4T (G►2C), G►151T (G►51C) and 8 nucleotide substitution that led to a unique SSKGG►TLNSE amino acid change in UPM08136. In the fibre gene, there were C►392G, G►393C (A►131G), C►430A, T►432C (R►144S), and T►434G, G►435C (L►145C) in UPM11142 isolate; synonymous G►431C and A►445G (R►144T) in UPM11134; and A►381T (L►127F), G►429T, A►430C and C►432T (L►143F, (S►144R) in UPM08136 isolates. The CEL cells adapted well to Cytodex 1® microcarrier with cell attachment to the microcarrier within 3 hours of incubation. CPE, cell detachment and high titre were indicative of virus growth in the Cytodex™ 1 microcarrier adapted CEL cells maintained in a stirred tank bioreactor. No clinical signs, mortality, gross and histopathologic changes of organs were recorded among chickens in the control group and chicken groups inoculated with inactivated and attenuated FAdV 8b strains (with or without booster). But chickens in control challenged group showed signs of depression and inappetence at 1 to 2 days post challenge and recorded enlarged and congested liver, spleen and thymus. The control challenged group had lower (p<0.05) body weight than the chickens inoculated with inactivated UPM11142P5B1 (with or without booster) challenged groups at 42 dpi. Inoculated chickens (with or without booster) had higher (p>0.05) FAdV antibodies titre than the control group on 7, 35 and 42 dpi, while the chickens with UPM11142P5B1 had higher (p<0.05) at 28 dpi. Inoculated challenged groups recorded high antibody titre at 35 and 42 dpi. The T cells were higher in chicken groups inoculated with inactivated UPM11142P5B1 and UPM08136P5B1 with or without booster in the liver, spleen and thymus, with CD8+ T cells being higher (p<0.05) at 21 dpi in the liver and spleen than in the uninoculated control chickens. The T cells were also higher at 35 and 42 dpi in the liver, spleen and thymus of inoculated challenged chickens than those of the challenged control chickens. The copy number of the FAdV challenge virus was significantly higher (p<0.05) in the liver and cloaca of challenged control chickens than in chicken groups inoculated with inactivated UPM11142P5B1 and UPM08136P5B1 with or without booster. The control challenged group had lower (p<0.05) body weight than the chickens on the attenuated challenged groups (UPM11142P20B1 and UPM08136P20B1) at 35 and 42 dpi. There was higher FAdV antibody titre among chicken inoculated with live attenuated FAdV with or without booster using attenuated or inactivated FAdV on days 7, 21, 35, and 42 pi than the control group. There was no significant difference (p>0.05) in the antibody titre induced by UPM11142P20B1 and UPM08136P20B1 live attenuated viruses throughout the trial. There was higher CD3+. CD4+ and CD8+ T cells in the liver, spleen and thymus of chickens inoculated with attenuated UPM11142P20B1 and UPM08136P20B1 without booster, with live attenuated or inactivated FAdV booster than the uninoculated non-challenged chickens, and similar results were recorded among the challenged groups. The copy number of the FAdV challenge virus was significantly higher in the liver and cloaca of challenged control chickens at 35 and 42 dpi than that of chickens inoculated with attenuated FAdV strains, and with (inactivated and attenuated) and without booster. In conclusion, the three FAdV isolates from field outbreaks of IBH showed high pathogenicity in CEE and CEL cells, were successfully attenuated in CEL cells and molecularly characterised. The changes in the hexon and fibre genes of the P20 isolates are the markers for attenuation. CEL cells adapted well to Cytodex™ 1 microcarrier and were used successfully to propagate P5 and P20 isolates of UPM11142 and UPM08136 in stirred tank bioreactor without molecular changes. The inactivated (P5B1) and attenuated (P20B1) FAdVs were safe and induced humoral and cellular immunity in commercial broiler chickens which provided protection against pathogenic FAdV 8b challenge, reduced viral load in the liver and shedding in cloaca. Therefore, the attenuated and inactivated FAdV UPM11142 and UPM08136 isolates in the present study have high potential as FAdV serotype 8b vaccine candidates for the control and prevention of IBH in chickens.